1995
DOI: 10.1128/jcm.33.5.1129-1135.1995
|View full text |Cite
|
Sign up to set email alerts
|

Cluster of oral atypical Candida albicans isolates in a group of human immunodeficiency virus-positive drug users

Abstract: Twenty-one chlamydospore-forming and germ tube-positive Candida albicans clinical isolates from 15 human immunodeficiency virus (HIV)-positive and 3 HIV-negative patients were examined by two different genetic methods. Multilocus enzyme electrophoresis and hybridization with the C. albicans-specific Ca3 probe showed that such isolates can be split into two genetically distinct groups that can be clearly distinguished. One group mainly contained strains with atypical sugar assimilation patterns and could be dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 24 publications
2
57
0
1
Order By: Relevance
“…In the last few years, several research groups have reported the recovery of many atypical isolates of C. albicans in clinical samples. 2,[6][7][8][9][10] Atypical isolates, such as C. africana, differ from most typical C. albicans strains because one or more phenotypic characteristics are clearly different. These atypical strains are often difficult to recognise by routine methods and they may represent variants of C. albicans or even new species as C. dubliniensis.…”
Section: Resultsmentioning
confidence: 99%
“…In the last few years, several research groups have reported the recovery of many atypical isolates of C. albicans in clinical samples. 2,[6][7][8][9][10] Atypical isolates, such as C. africana, differ from most typical C. albicans strains because one or more phenotypic characteristics are clearly different. These atypical strains are often difficult to recognise by routine methods and they may represent variants of C. albicans or even new species as C. dubliniensis.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are in accordance with other studies. 5,16 As phenotypic assays may demonstrate different results in identifying C. dubliniensis we also performed PCR with speciesspecific primers for C. dubliniensis. In our test conditions all suspected isolates were positive with primers DUBF and DUBR in accordance with Donnelly et al 18 We found four (11.4%) isolates in our patient group as C. dubliniensis.…”
Section: Discussionmentioning
confidence: 99%
“…Atypical candidal isolates have recently been reported from the oropharyngeal region of HIV-seropositive drug users(5). Despite showing similarities with C. albicans, namely a positive germ-tube test and the production of chlamydospores, such isolates showed abnormal sugar assimilation profiles that did not correspond to any known yeast species.…”
mentioning
confidence: 99%